Reversal of thoracic sympathectomy through robot‐assisted microsurgical sympathetic trunk reconstruction with sural nerve graft and additional end‐to‐side coaptation of the intercostal nerves: A case report. Issue 8 (22nd July 2021) - Chang, Tommy Nai‐Jen; Daniel, Bassem W.; Hsu, Angela Ting‐Wei; Chen, Lisa Wen‐Yu; Sung, Cheyenne Wei‐Hsuan; Chuang, David Chwei‐Chin; Chao, Yin‐Kai
Abstract: Thoracic sympathectomy to treat palmar hyperhidrosis (PH) has widely been performed. Many patients regret the surgery due to compensatory hyperhidrosis (CH), gustatory hyperhidrosis, arrhythmia, hypertension, gastrointestinal disturbances, and emotional distress. Robotic applications in microsurgery are very limited. We report the technique and long‐term patient‐reported outcomes of bilateral robot‐assisted microsurgical sympathetic trunk reconstruction with a sural nerve graft in an interdisciplinary setting. A 59‐year‐old female suffered from severe adverse effects after endoscopic thoracic sympathectomy (ETS) for PH 25 years ago. She reported CH over the whole trunk, gustatory hyperhidrosis, excessive dry hands, and emotional distress. An interdisciplinary surgical team performed a bilateral sympathetic trunk reversal reconstruction with an interpositional sural nerve graft per side by a da Vinci® Robot. The nerve graft was microsurgically coapted using 9–0 sutures end‐to‐end to the sympathetic trunk stumps and side‐to‐end to the intercostal nerves T2–T4. At 24, 33 and 42 months, palmar dryness and emotional distress were strongly reduced. A highly specialized interdisciplinary setting may provide a precise, safe, and efficient treatment for ETS sequelae. A clinical study is initiated to validate this new therapy.